Helium adsorbed on carbon nanotube bundles: one-dimensional and/or two-dimensional solids? Physics in Quantum Crystals - Wilson, Tate; Vilches, Oscar E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Heat capacity measurements of 4He adsorbed on closed-end single-wall carbon nanotube bundles in the temperature range 1.5 K < T < 6 K are reported. Heats of adsorption Qst calculated from isotherms measured on the same calorimeter cell are included. We correlate Qst features with features of the helium heat capacity. We discuss possible interpretations of the current data.